If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(1M) + (-2N) = 0 Remove parenthesis around (1M) x * 1M + (-2N) = 0 Reorder the terms for easier multiplication: 1x * M + (-2N) = 0 Multiply x * M 1xM + (-2N) = 0 Reorder the terms: (-2N) + 1xM = 0 Solving (-2N) + 1xM = 0 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-1xM' to each side of the equation. (-2N) + 1xM + -1xM = 0 + -1xM Combine like terms: 1xM + -1xM = 0 (-2N) + 0 = 0 + -1xM (-2N) = 0 + -1xM Remove the zero: (-2N) = -1xM Divide each side by '-2'. N = 0.5xM Simplifying N = 0.5xM
| 2/3x2-5= | | 3p+6=78 | | 2/3x-5=-2 | | C(t)=2x+180 | | 5x-5y+7a= | | 3=-3/2(x+6) | | Ic(t)=2x+180 | | 16=4(2x+1) | | x-1/2=1/4 | | y^1/7 | | -9=x+20 | | 14=s-61 | | k/-4=3 | | q+5=8(q+7) | | -20=-2+3v | | 6a^2+4a=-11 | | 25-6x=19-5x | | 6m^2+13=5 | | .05x/259y=5550 | | .05x*259y=5550 | | 4x+28=10 | | 18=4w+2 | | .40x+1.25y=150 | | sinx+-1cosx+-1tanx=-1 | | 3y+4x-Y-2x-5y= | | 3(-6+9)+10x=1 | | x-4-3x-7=1/4 | | 4+7n+5n= | | 5x-12=8(x+3) | | 2a+a+5a= | | 55=4v+15 | | 7/9-4/6 |